1973
DOI: 10.1530/jrf.0.0350211
|View full text |Cite
|
Sign up to set email alerts
|

The Fertility of Heifers Inseminated at Predetermined Intervals Following Treatment With Mga and HCG to Control Ovulation

Abstract: Oestrus and the time of ovulation were controlled in eighty-seven mature non-pregnant heifers by using silastic implants of MGA followed by an injection of HCG 48 hr after removal of the implants. The heifers were allocated at random to three groups and inseminated with frozen semen before the estimated time of ovulation. Animals in Groups 1 and 2 were inseminated once at 14 and 24 hr, respectively, after HCG while animals in Group 3 were inseminated twice 14 and 24 hr after HCG. All heats observed after insem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The FSH-activity of hCG is well known and may be reflected in the higher ovulation rates in Groups 3 and 4 in Exp. A. Suppression of oestrus in a high proportion of animals is a feature of the results of many experiments in which hCG has been used for the control of ovulation in farm animals (Braden et al, 1960;Roche & Crowley, 1973). This effect was also apparent in the present work.…”
Section: Discussionsupporting
confidence: 74%
“…The FSH-activity of hCG is well known and may be reflected in the higher ovulation rates in Groups 3 and 4 in Exp. A. Suppression of oestrus in a high proportion of animals is a feature of the results of many experiments in which hCG has been used for the control of ovulation in farm animals (Braden et al, 1960;Roche & Crowley, 1973). This effect was also apparent in the present work.…”
Section: Discussionsupporting
confidence: 74%
“…Oestrus and ovulation can be synchronized in cows with progestagens but the conception rate to matings at the controlled oestrus is lower than normal (Hansel, 1967;Mauléon & Chupín, 1971; Jochle, 1972;Roche & Crowley, 1973). When the period of progestagen treatment is reduced to 10 days, by giving an injection of oestrogen on the 1st day of progestagen treatment to induce premature regression of the CL, the conception rate has been reported to be normal (Wiltbank & Kasson, 1968;Wiltbank, Sturges, Wideman, Le Fever & Faulkner, 1971; Chupín, Le Provost, Mauléon, Ortavant, Parez & Petit, 1972;Roche, 1974a).…”
Section: Introductionmentioning
confidence: 99%
“…Long-term progestagen treat¬ ments have resulted in reduced fertility levels at the controlled oestrus (Jochle, 1972). The use of oestrogens (Ulberg & Lindley, 1960;Hansel et al, 1961) and Oestrous cycle control in heifers 369 gonadotrophins (Graves & Dziuk, 1968;Boyd & Tasker, 1971;Roche & Crowley, 1973) in association with long-term progestagen treatments and fixedtime insemination procedures have generally resulted in further reductions in conception rates. Recent reports have indicated that if the period of progestagen treatment is reduced to about 10 days, fertility levels are normal at the con¬ trolled oestrus (Wiltbank & Kasson, 1968;Wishart & Young, 1974;Roche, 1974;Sreenan, 1975).…”
mentioning
confidence: 99%